PENERAPAN MODEL COOPERATIVE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE PADA MATERI BUNYI DAN INDERA PENDENGARAN - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This research wanted to identify whether the implementation of Cooperative Snowball Throwing could increase the achievements of the fourth grade students of MIN 42 Pidie in learning the topic sound and hearing sense. This research was a Classroom Action Research. It was done in three cycles. The data was collected by involving four main steps : Planning, Implementing, Observing and Reflecting. The results described in qualitative data analyzing. It was found that the average scores of the students increased significantly in each cycle. Cycle I : 70.23, cycle II : 81.36 and cycle III : 87. 27. Moreover, the students’ participation in learning was also gradually growth. Thus, the implementation of Cooperative Snowball Throwing could improve the students’ achievements in learning.